Tooth Decay in Alcohol Abusers Compared to Alcohol and Drug Abusers - Ananda P. Dasanayake; Saman Warnakulasuriya; Colin K. Harris; Derek J. Cooper; Timothy J. Peters; Stanley Gelbier (Hindawi Limited, 2010)
Alcohol and drug abuse are detrimental to general and oral health. Though we know the effects of these harmful habits on oral mucosa, their independent and combined effect on the dental caries experience is unknown and worthy of investigation. We compared 363 "alcohol only" abusers to 300 "alcohol and drug" abusers to test the hypothesis that various components of their dental caries experience are significantly different due to plausible sociobiological explanations. After controlling for the potential confounders, we observe that the "alcohol and drug" group had a 38% higher risk of having decayed teeth compared to the "alcohol only" group (𝑃<.05). As expected, those who belonged to a higher social class (OR=1.98; 95%  CI=1.43-2.75) and drank wine (OR=1.85; 95%  CI=1.16-2.96) had a higher risk of having more filled teeth. We conclude that the risk of tooth decay among "alcohol only" abusers is significantly lower compared to "alcohol and drug" abusers.